Noumenal Power - Forst, Rainer (2014)
In political or social philosophy, we speak about power all the time. Yet the meaning of this important concept is rarely made explicit, especially in the context of normative discussions. But as with many other concepts, once one considers it more closely, fundamental problems arise, such as whether a power relation is necessarily a relation of subordination and domination. In the following, I suggest a novel understanding of what power is and what it means to exercise it.